Unveiling hidden sponge biodiversity within the Hawaiian reef cryptofauna - Jan Vicente (2022)
Our perception of reef diversity is dominated by corals, fish, and a few other groups that visibly dominate the reef surface. However, the bulk of reef biodiversity resides within the reef framework, and this cryptobiota is fundamentally important for the surface community. Sponges are abundant and conspicuous on the reef surface in productive, continental reefs, but largely vanish from surveys of the oligotrophic reefs of Oceania. However, their diversity in the cryptobiota remains poorly characterized. Here, we explore the contribution of cryptobenthic sponges to overall sponge diversity on 1750 m2 of reef habitat in Kāneʻohe Bay and Waimanalo in the island of Oʻahu, Hawaiʻi. We also assessed cryptic sponges using 15 m2 of autonomous reef monitoring structures (ARMS) deployed in this same area. We used integrative taxonomy combining morphology, COI and 28S barcoding to delineate and track species, most of which are poorly known or undescribed. We documented 186 OTUs, 150 of which are new records for the Hawaiian Islands, increasing the known sponge fauna of Kāneʻohe Bay by 3.5-fold, and that of the Hawaiian Islands by 2.5-fold. More than ¾ of the sponge OTUs were cryptobenthic. Reef sampling provided access to 31% (44 OTUs), whereas 52% (75 OTUs) were retrieved exclusively from ARMS. These results illustrate that the interstices of ARMS units provide suitable habitat for settlement of cryptobenthic sponges that would otherwise be impossible to access through traditional field surveys. Tracking species with provisional names, using integrative species delineation anchored to vouchers, images, and DNA barcodes provides a powerful approach for working with such a poorly understood fauna.